Selective flotation separation of fluorite from calcite by using sesbania gum as depressant. (1st December 2021) - Wei, Qian; Dong, Liuyang; Jiao, Fen; Qin, Wenqing
Graphical abstract: Highlights: Flotation separation of fluorite from calcite is difficult. Depressant sesbania gum is introduced to depress calcite. Flotation separation of fluorite from calcite can be achieved with sesbania gum. An adsorption model and separation model are finally obtained. Abstract: The effect of macromolecular depressant sesbania gum (SG) on the flotation separation of fluorite from calcite by using collector sodium oleate (NaOL) was studied. The flotation behavior of fluorite and calcite in the absence and presence of SG was studied through micro-flotation tests. The separation effect of SG on the two minerals was determined by artificial mixed mineral tests. Laboratory-scale flotation tests were used to verify the separation efficiency of SG in the flotation separation of the two minerals. The selective depressive mechanism of SG was revealed by Fourier transform infrared (FTIR) analysis, wettability analysis and X-ray photoelectron spectroscopy (XPS) analysis. Micro-flotation experiments indicated that SG could efficiently realise the flotation separation of fluorite from calcite. Laboratory-scale flotation tests showed that good beneficiation indices with CaF2 grade of 76.15% and CaF2 operating recovery of 96.23% of rough concentrates were obtained by adding 100 g/t SG at pH 9. Mechanism experiments revealed that the adsorption of SG on the surface of calcite was stronger than that of fluorite. SG was not only adsorbed on the surface of calcite through hydrogen bonds but also chemically adsorbed on calcium ion sites on the surface of calcite. As a result, the active sites on the surface of calcite were reduced, it was not conducive to the adsorption of NaOL and it depressed the flotation of calcite. However, SG only formed the hydrogen bond through its own hydroxyl group and the electronegative F − on the surface of fluorite to adsorb on the surface of fluorite. Therefore, the selective adsorption of SG on the surface of fluorite and calcite was the reason for its selective inhibition of the two minerals.